1991
DOI: 10.1152/jn.1991.65.3.639
|View full text |Cite
|
Sign up to set email alerts
|

Long-term potentiation of nicotinic transmission by a heterosynaptic mechanism in the stellate ganglion of the cat

Abstract: 1. In the anesthetized, scopolamine-treated cat, the compound action potential (CAP) evoked by a single supramaximal shock to the third thoracic white ramus (T3WR) was recorded in the inferior cardiac nerve (ICN). The CAP was depressed in a dose-dependent manner by the intravenous administration of the nicotinic antagonist hexamethonium (C6). 2. During steady intravenous infusion of C6, which reduced the amplitude of the CAP by 80-90%, a short train of stimuli (few seconds, 10-40 Hz) to the sympathetic trunk j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Evidence for involvement of the postsynaptic region is indicated by the role of carbon monoxide as retrograde transmitter in the induction of gLTP (Alkadhi et al 2001a, b; see review Alkadhi et al 2005a, b). Although earlier experiments in rat SCG suggest no involvement of the postsynaptic membrane (Briggs et al 1985), later it is shown in a variety of sympathetic ganglia from various species that the postsynaptic is, indeed, involved (Bachoo and Polosa 1991;Morales et al 1994).…”
Section: Discussionmentioning
confidence: 85%
“…Evidence for involvement of the postsynaptic region is indicated by the role of carbon monoxide as retrograde transmitter in the induction of gLTP (Alkadhi et al 2001a, b; see review Alkadhi et al 2005a, b). Although earlier experiments in rat SCG suggest no involvement of the postsynaptic membrane (Briggs et al 1985), later it is shown in a variety of sympathetic ganglia from various species that the postsynaptic is, indeed, involved (Bachoo and Polosa 1991;Morales et al 1994).…”
Section: Discussionmentioning
confidence: 85%
“…As noted above, all that is normally necessary to achieve ganglion blockade is to reduce the amplitude of strong EPSPs to below ganglion cell threshold. Indeed, Bachoo and Polosa 9 showed that potentiated ganglionic transmission of this type in the cat stellate ganglion could partly restore the potency of nicotinic inputs that had been reduced by hexamethonium treatment. To what extent the new enhanced state allowed summation of subthreshold EPSPs, or merely lowered ganglion cell threshold sufficiently for attenuated nicotinic (or other) EPSPs to trigger action potentials, we cannot say.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of gLTP is not dependent on the activation of adrenergic, cholinergic, dopaminergic, or adenosine receptors (5,6,28,34,35). Recent evidence strongly suggests that gLTP in the rat SCG is strictly dependent on the activation of serotonin 5-HT 3 receptor (13).…”
Section: Characteristics Of Gltpmentioning
confidence: 98%
“…Additionally, gLTP has been measured in ganglia in anesthetized animals in situ (10,11,28,136). The gLTP of the nicotinic pathway has been reported in various autonomic ganglia from various animal species, including rat SCG (4,8,13,29), cat SCG, lumbar and stellate ganglia (10,28,30), guinea pig SCG (12,31), chick parasympathetic ciliary ganglion (14), and bullfrog sympathetic ganglia (7,23,32,33).…”
Section: Activity-dependent Gltp Of the Nicotinic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation